Relationship Between Levels Of Formal Education And Pregnant Women's Knowledge About Care Of New Birth At Hana Kasih Clinic In 2021 - Rizky Andriani Bakara (Science Midwifery, 2021)
The background of formal education is very influential on all aspects of the lives of mothers from the perspective of thoughts, feelings and actions. The higher the education level of a mother, the higher the mother's basic ability to care for her baby. This study aims to determine the relationship between the level of formal education and knowledge of pregnant women about newborn care. The research method used isanalytical observationwith a cross-sectional approach method. Where the population is 35 pregnant women and the sampling technique is accidental sampling, so the number of samples is 35 pregnant women. The results of the analysis showed that from 35 pregnant women the majority there were 18 pregnant women with basic education the majority had less knowledge as many as 18 people (51%). The results of the Chi-Square test obtained a value of = 0.000, this means that the p-value is smaller than (0.05), which means that there is a relationship between the level of formal education and knowledge of pregnant women about newborn care. It is expected that health workers at the Bunda Kabanjahe Clinic will provide counseling about newborn care and pregnant women to increase knowledge about newborn care.